ОСОБЕННОСТИ УПРАВЛЕНИЯ ПРЕОБРАЗОВАТЕЛЯМИ ПОСТОЯННОГО ТОКА - Жуйков, В.Я.; Вербицкий, Е.В. (Інститут електродинаміки НАН України, Київ, 2012)
Features direct current converter are analyzed. Possibility origin of self-excited oscillations are researched. Method ofimproving output voltage quality parameters are proposed. References 1, figures 4.